The Effictiveness of a Training Program Based on Future Thinking in Developing Motivation for Academic Achievement for a Sample of Mutah University Students - Ahmad Abdullah Al-Tarawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to examine effectiveness of a proposed training program based on future thinking in developing motivation for academic achievement among a sample of Mutah University students. The study followed quasi-experimental methodology and consisted of 70 college students who were divided equally into experimental and control groups; after they were selected in a purposive way during second semester in 2017/ 2018. The study used a proposed training program and an academic motivational scale after ensuring that they were valid and reliable. The individuals of experimental group received the trining program for two months; twice weekly. The results showed that there were significant statistical differences between experimental and control groups in dimensions of academic motivational scale and a total score of scale in favor of the experimental group. The study recommends to expand the usage of the proposed training program with the students of the college of education at Mutah University to help them in raising ambition level of due to its effect on all components of academic motivation for achievement.